Assessing and improving safety culture throughout an academic medical centre: a prospective cohort study. Issue 6 (2nd December 2010) - Paine, Lori A; Rosenstein, Beryl J; Sexton, J Bryan; Kent, Paula; Holzmueller, Christine G; Pronovost, Peter J
Abstract : Objectives: To describe the authors' hospital-wide efforts to improve safety climate at a large academic medical centre. Design and setting: A prospective cohort study used multiple interventions to improve hospital-wide safety climate. 144 clinical units in an urban academic medical centre are included in this analysis. Interventions: The comprehensive unit-based safety programme included steps to identify hazards, partner units with a senior executive to fix hazards, learn from defects, and implement communication and teamwork tools. Hospital-level interventions were also implemented. Main outcome measures: Safety climate was assessed annually using the safety attitudes questionnaire. The safety culture goal was to meet or exceed the 60% minimum positive score or improve the score by ≥10 points. Results: Response rates were 77% (2006) and 79% (2008). For safety climate, 55% of units in 2006 and 82% in 2008 achieved the culture goal. For teamwork climate, 61% of units in 2006 and 83% in 2008 achieved the culture goal. The mean safety climate improvement (difference score) for 79 units at or above 60% in 2006 was 0.201 in 2008; the mean improvement for the 65 units below the threshold was 18.278. The mean teamwork climate improvement (difference score) for the 89 units at or above 60% in 2006 was 0.452 in 2008; the mean improvement for the 55 units below the threshold was 16.176. Climate scores improved significantly from 2006 to 2008 in every domain except stress recognition. Conclusions: Hospital-wide interventions were associated with improvements in safety climate at a large academic medical centre.